Serum cytokine profiling reveals different immune response patterns during general and severe Mycoplasma pneumoniae pneumonia - Zhang, Zhikun; Dou, Haiwei; Tu, Peng; Shi, Dawei; Wei, Ran; Wan, Ruijie; Jia, Chunmei; Ning, Lihua; Wang, Dongmei; Li, Jing; Dong, Yan; Xin, Deli; et al. (Frontiers in Immunology, 2022)
Mycoplasma pneumoniae (MP) is an important human pathogen that mainly affects children causing general and severe Mycoplasma pneumoniae pneumonia (G/SMPP). In the present study, a comprehensive immune response data (33 cytokines) was obtained in school-age children (3–9 years old) during MPP, aiming to analyze the immune response patterns during MPP. At acute phase, changes of cytokines were both detected in GMPP (24/33) and SMPP (23/33) groups compared to the healthy group (p < 0.05), with 20 identical cytokines. Between MPP groups, the levels of 13 cytokines (IL-2, IL-10, IL-11, IL-12, IL-20, IL-28A, IL-32, IL-35, IFN-α2, IFN-γ, IFN-β, BAFF, and TSLP) were higher and three cytokines (LIGHT, OPN and CHI3L1) were lower in the SMPP group than in the GMPP group (p < 0.05). Function analysis reveals that macrophage function (sCD163, CHI3L1) are not activated in both MPP groups; difference in regulatory patterns of T cells (IL26, IL27, OPN, LIGHT) and defective activation of B cells (BAFF) were detected in the SMPP group compared to the GMPP group. Besides, the level of osteocalcin; sIL-6Rβ and MMP-2 are both decreased in MPP groups at acute and convalescent phases compared to the healthy group, among which the levels of sIL-6Rβ and MMP-2 showed negative correlations (p < 0.1) to the application of bronchial lavage in SMPP group, indicating their roles in the development of MPP. At the convalescent phase, more cytokines recovered in GMPP (18) than SMPP (11), revealing better controlled immune response during GMPP. These results reveal different immune response patterns during GMPP and SMPP. In addition, the differentiated cytokines may serve as potential indicators of SMPP; early intervention on immune response regulations may be helpful in reducing the severity of SMPP.